The Effect of LAB Inoculants on The Chemical and Microbial Composition in Fermentation of TMR Silage - Wahyudi, Ahmad; Sutawi, Sutawi; Hendrianingsih, L. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The effect of applying lactic acid bacteria (LAB) at ensiling on the nutrition and microbial composition in fermentation total mixed ration (TMR) silage was studied under laboratoryconditions. The LAB inoculants consisted of Lactobacillus plantarum (P1) commercial and two othersLactobacillus that isolated from local corn leaf (P2 and P3) in experiments with TMR (11% CP and68% TDN). The inoculants were applied each at about 106 cfu g. After treatment, the TMR wereensiled in 1 lt anaerobic jars. Six jars per treatment were sampled on days 21. At the end of theexperiment, the silages were subjected to chemical and microbiological parameters, to determinethe nutritive value and contaminant microbes compare with no LAB inoculation. In TMR silages, theLAB inoculants did not affect the nutritive value (dry matter, organic matter, crude protein, extractether, and crude fiber) however its increase LAB population and depress the contaminant microbes(aerob bacteria, yeast, and clostridia). Inoculants P3 from corn leaf seem to have the most potentialin protecting TMR from undesirable microbes. Key Words: LAB, Chemical and Microbial Composition, TMR, Silage